DEVELOPMENT OF TEMPERATURE-BASED MODEL FOR PREDICTING PHENOLOGY OF RICE (ORYZA SATIVA) IN CENTRAL AGRO-CLIMATIC ZONE OF PUNJAB - KAUR, PRABHJYOT; KHEHRA, MANDEEP KAUR; HUNDAL, S.S. (Annals of Agricultural Research, 2014)
Field experiments were conducted during four consecutive kharif seasons of 1999-2002 at Ludhiana (Punjab) to evaluate the effect of temperature on phenological development of rice crop sown on two dates (D1-2nd week of May and D2-4th week of May). Rice cv. PR-114 attained physiological maturity in 128 to 138 days for first date of sowing and 135 to 143 days for second date of sowing. The growing degree days required from nursery sowing to physiological maturity ranged from 2644 to 2894 ÂºC days for first date of sowing and 2736 to 2814ÂºC days for second date of sowing with a coefficient of variation of 2.75%. A linear regression model was derived based on phenophasic data on temperature for predicting the onset of a particular phenophase of the crop.